Analysis of therapeutic resources in elderly patients with knee osteoarthritis: literature review (Research, Society and Development, 2021)
Knee osteoarthritis (OA) is a pathology of a degenerative order, which occurs because of several factors. In the world there are 50 million people in this condition, physiotherapy has several techniques to treat these individuals among those already known, electrophotothermotherapy and kinesiotherapy. The study seeks approaches that can be applied in evidence-based clinical practice. The research emerges through the PICO strategy: Elderly, therapeutic resources, conservative treatment, osteoartitis of the knee. Applying a Boolean AND operator to maximize results, with 268 articles found in Google Scholar, Scielo, MEDLINE / PubMed. The results were inserted in separate tables for better teaching and understanding of the research. It was concluded that physiotherapy has much broader resources than electrothermal phototherapy and kinesiotherapy, all the resources found can be applied inside and outside the environment of the physiotherapy clinic with specific objectives regarding the degree of OA.